Automation of Healthcare Management Systems in the U.S. Using Information Technology and Artificial Intelligence - Bhuiyan, Md Fakhrul Hasan; Hosen, Arif; Vanu, Nur; Riipa, Muslima Begom; Hossain , Mohammad; Prabha, Mani; Hassan , Ali; Semi, Mst Masuma Akter (Journal of Posthumanism, 2025)
Background: The integration of Artificial Intelligence (AI) and Information Technology (IT) into healthcare management systems (HMS) has shown promise in automating administrative and operational processes, addressing inefficiencies, reducing costs, and improving patient outcomes. However, stakeholder perceptions and challenges associated with adoption remain inadequately explored. Objective: This study aims to evaluate the perceptions, benefits, and challenges of implementing AI and IT solutions in HMS, focusing on their impact on efficiency, user satisfaction, economic implications, and ethical concerns. Methodology: A cross-sectional design was employed, using a structured questionnaire distributed to 103 participants, including administrators, clinicians, IT professionals, and patients. Quantitative data were analyzed using descriptive statistics, correlation, and regression analyses to identify trends and relationships among variables such as automation, accuracy, and safety concerns. Results: The study reveals a moderate level of AI and IT awareness in healthcare management (M = 3.07, SD = 0.95). While AI is perceived as beneficial (M = 3.59, SD = 0.89), concerns about ethical and security issues (r = 0.454, p < 0.01) persist. Significant predictors of AI expectations include ethical concerns (β = 0.399, p < 0.01) and implementation challenges (β = 0.359, p < 0.01). Conclusion: AI has the potential to revolutionize healthcare management, but addressing barriers such as usability, cost, and ethical challenges is critical. Collaborative strategies and regulatory frameworks are essential to maximize AI’s impact and foster sustainable adoption in healthcare systems